2015
DOI: 10.1007/s12237-015-0055-z
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Submerged Aquatic Vegetation Expansion on a Declining Turbidity Trend in the Sacramento-San Joaquin River Delta

Abstract: Submerged aquatic vegetation (SAV) has welldocumented effects on water clarity. SAV beds can slow water movement and reduce bed shear stress, promoting sedimentation and reducing suspension. However, estuaries have multiple controls on turbidity that make it difficult to determine the effect of SAV on water clarity. In this study, we investigated the effect of primarily invasive SAV expansion on a concomitant decline in turbidity in the Sacramento-San Joaquin River Delta. The objective of this study was to sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 54 publications
2
80
0
Order By: Relevance
“…E. densa beds create drag and slow-moving water, reducing turbulence, and increasing net deposition of sediment, thereby increasing water clarity (Yarrow et al 2009). Hestir et al (2015) found that, 21% to 70% of the increase in water clarity in the Delta from 1975 to 2008 can be attributed to SAV expansion. The dense canopies of E. densa beds shade the water column, contributing to light limitation of phytoplankton and benthic algae.…”
Section: Submerged Aquatic Vegetationmentioning
confidence: 96%
“…E. densa beds create drag and slow-moving water, reducing turbulence, and increasing net deposition of sediment, thereby increasing water clarity (Yarrow et al 2009). Hestir et al (2015) found that, 21% to 70% of the increase in water clarity in the Delta from 1975 to 2008 can be attributed to SAV expansion. The dense canopies of E. densa beds shade the water column, contributing to light limitation of phytoplankton and benthic algae.…”
Section: Submerged Aquatic Vegetationmentioning
confidence: 96%
“…SAV, floating vegetation, and decreased sediment supply from the watershed may explain observed decreases in turbidity (Hestir et al 2016). Given the potential strong feedback between increased clarity and increased SAV, these changes may be an important aspect of the future Delta.…”
Section: Information Gapsmentioning
confidence: 99%
“…An example of biota affecting transport is invasive SAV in Delta channels. SAV began increasing significantly in the 1970s, and sites that now have greater SAV coverage had a greater turbidity decline in the later 20th century (Hestir et al 2016). SAV can slow water movement and reduce bed shear stress, promoting sedimentation and reducing SSC.…”
Section: Biogeochemical Forcingmentioning
confidence: 99%
See 2 more Smart Citations